(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Data security is a top priority in today’s digital world, especially when dealing with sensitive information kept in databases. Hybrid encryption systems, which integrate various encryption algorithms, have grown in popularity due to their capacity to improve data security. This study compares and contrasts several encryption methods used in hybrid database implementation strategies. The study begins with a review of data encryption foundations and then presents the notion of hybrid encryption, emphasizing its benefits in attaining strong security. Following that, a thorough examination of popular encryption methods such as Advanced Encryption Standard (AES), Data Encryption Standard (DES), Rivest-Shamir-Adleman (RSA), and Elliptic Curve Cryptography (ECC) is performed. The comparison includes critical variables such as security strength, key size, encryption/decryption speed, resource needs, mathematical difficulty, key management, adoption/standardization, algorithm maturity, regulatory compliance, flexibility, known weaknesses, and patent/license status. Finally, this comparison research provides significant insights into the strengths and shortcomings of various encryption algorithms in the context of hybrid strategies for database implementation.